Education on Antibiotic Use to Prevent Resistance in Lengkongbarang Village Tasikmalaya Regency - Anisa Pebiansyah; Hendra Komara; Adil Cipta Mahardika; Febby Nuzuliyah Ramadhanti; Dona Fitriani; Aulia Oktavianti; Cahya Kamila (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The irrational use of antibiotics can lead to drug resistance, which is a global health problem. Counseling the community about the proper use of antibiotics is very important to prevent antibiotic resistance. This study aims to improve the knowledge of the Lengkongbarang Village community regarding the proper use of antibiotics to prevent drug resistance. Counseling was conducted in July 2024 in Lengkongbarang Village with a cross-sectional approach. A total of 15 respondents aged 17 years and above participated in this activity. Pretest and posttest were used to assess the level of knowledge of respondents before and after counseling. Data were analyzed using paired t-tests to see the increase in respondents' knowledge. Results showed a significant increase in respondents' knowledge regarding the rational use of antibiotics. The average pretest score was 51.33, while the average posttest score increased to 64.00. The statistical test showed a p-value of 0.020, indicating a significant difference between the pretest and posttest scores. This counseling succeeded in increasing the knowledge and understanding of the Lengkongbarang Village community regarding the appropriate and rational use of antibiotics. Hopefully, this knowledge can be applied in daily life to prevent drug resistance.